Comparative theoretical study between chaos theory and innovation process - Souza, Crisomar Lobo de; Kuniyoshi, Márcio Shoiti; Freitas, Adriana Buarque de Gusmão Gomes de (Pensamento & Realidade, 2020)
This article aims to make a correlation between chaos theory and the innovation process. Unlike what the name seems to be, chaos theory is linked to discovering simple patterns and laws that govern several complex phenomena. The complex is also innovation; therefore, this article makes an analogy of the innovation process from its conception to its implementation in the market with three principles of chaos theory: system, nonlinearity, and complexity. The innovative organization is characterized by constant innovation and complexity in nature. Uncertainty is an essential feature of innovation, which means an inability to predict the prospecting processor's outcome to set the best way to achieve a goal. Unpredictability is one of the characteristics of chaotic systems in which any minimal initial change in their conditions causes drastic changes in their course. Based on these premises, analogies were made to serve as a basis for further studies.